Reliability of the Turning Point Core Trainer as a Measure of Shoulder Hip Separation Angle, Shoulder Angular Velocity, and Hip Angular Velocity During Volleyball Spiking Actions - Alsarraf, Bader J; Brown, Justin R; Waller, Mike; Eisenman, Patricia; Hicks-Little, Charlie A (Journal of Sports Research, 2015)
Separation of the shoulders and hips is an important contributor for rotational sports such as baseball and golf. Most recent has utilized Motion Capture technology. A new instrument has been developed as a tool to measure separation angle and can also be used to train the core musculature. The primary aim of the current study was to examine the reliability of shoulder hip separation angle (SHSA), shoulder angular velocity (SAV), and hip angular velocity (HAV) as measured using the Turning Point Core Trainer (TP) during volleyball spiking actions. Voluntary participants included 14 collegiate, Division I, female volleyball players from the University of Utah, ranging from 18-30 years of age. Participants completed 10 volleyball spike actions will fastened to the TP. SHSA was calculated at the height of the back swing. Participants were asked to provide maximal velocity during the forward phase thus providing SAV and HAV. Analysis for reliability demonstrated high Cronbach’s alpha coefficients across the 10 SHSA, SAV, and HAV (a =.98; a =.91; a =.94), respectively, indicating excellent internal consistency reliability for the TP. Follow-up research should examine whether or not training female outside hitters to increase SHSA at the top of the back swing, will increase SBV during either DL or DAC spikes. The TP measure of-axial rotation during spiking the internal consistency of the measures was high.